2020
DOI: 10.1021/acs.jpcc.0c07857
|View full text |Cite
|
Sign up to set email alerts
|

Nonempirical Definition of the Mendeleev Numbers: Organizing the Chemical Space

Abstract: Organizing a chemical space so that elements with similar properties would take neighboring places in a sequence can help to predict new materials. In this paper, we propose a universal method of generating such a one-dimensional sequence of elements, i.e. at arbitrary pressure, which could be used to create a well-structured chemical space of materials and facilitate the prediction of new materials. This work clarifies the physical meaning of Mendeleev numbers, which was earlier tabulated by Pettifor. We comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Because distance in feature space (e.g., in KRR) or latent space (i.e., in the ANN) is a critical component, prediction by ML models of new materials with compositions not well supported by training data is universally challenging. Nevertheless, RACs and other widely used representations 60 employ the nuclear charge in the representation, exaggerating differences between rows of the periodic table with respect to differences in group number 75 . While some heuristic properties in RACs (e.g., the Pauling electronegativity) more faithfully encode chemical similarity 64 , the nuclear-charge-based features are often emphasized in feature-selected subsets, highlighting their importance in model prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Because distance in feature space (e.g., in KRR) or latent space (i.e., in the ANN) is a critical component, prediction by ML models of new materials with compositions not well supported by training data is universally challenging. Nevertheless, RACs and other widely used representations 60 employ the nuclear charge in the representation, exaggerating differences between rows of the periodic table with respect to differences in group number 75 . While some heuristic properties in RACs (e.g., the Pauling electronegativity) more faithfully encode chemical similarity 64 , the nuclear-charge-based features are often emphasized in feature-selected subsets, highlighting their importance in model prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic radii and electronegativity are often quintessential for how chemistry is rationalized. 1,2 The history of quantifying the sizes of atoms under ambient conditions includes a large body of work, extending over the last one and a half-centuries (for a non-exhaustive summary of this history see references 3 and 4). One early motivation for attaining atomic and ionic sizes was to help understand X-ray diffraction patterns in terms of crystal structures, 5,6 another to provide a rationalization for metallization.…”
Section: Introductionmentioning
confidence: 99%
“…Mn is becoming increasingly important in phenomenological data-driven searches for new chemical compounds. More recently, Allahyari and Oganov (2020) revealed that a one-dimensional ordering using only atomic size and electronegativity allows the computation of a non-empirical Mn and the derivation of a universal sequence of elements.…”
Section: Chemical Periodicity Periodic Systems and Periodic Tablesmentioning
confidence: 99%